Конкурентоспособность гостиничного бизнеса. Проблемы и возможные пути их решения - Горбунов, Николай Петрович; Яценко, Ольга Николаевна (НТУ "ХПИ", 2014)
В статье проанализированы особенности гостиничного бизнеса, состояние его конкурентоспособности и факторы, влияющие на конкурентоспособность. Предложены пути развития гостиничного бизнеса и повышения его конкурентоспособности.

In the paper, the specificity of hotel business, the state of its competitiveness and the factors that affect the hotel competitiveness are analyzed. The ways for developing hotel business and enhancing its competitiveness are suggested.
Competitiveness of hotel business. Problems and possible ways of their decision
Keywords: гостиничные услуги; сфера услуг; экономика Украины; hotel services; hotel business